Narasi Hadis dalam Konten Dakwah Digital: Analisis Akun Youtube Ustadz Nuzul Dzikri - Ismail Nasution; Zulfirman Manik (Yayasan Salam Cerdas Al-Fattah, 2025)
The rise of digital da'wah in the social media era has profoundly reshaped the dissemination of Islamic teachings, particularly through platforms such as YouTube. This phenomenon underscores the importance of examining how hadith-based Islamic narratives are constructed within contemporary popular religious discourse. This study investigates the narrative construction of hadiths in the da'wah content of Ustadz Nuzul Dzikri on YouTube and explores how his communicative strategies influence the audience’s comprehension of hadith teachings. The research focuses on the selection, presentation, and interpretation of hadiths in his lectures, considering both the scholarly substance and rhetorical techniques employed. Adopting a qualitative methodology, this study utilizes content analysis as its primary method, with data gathered through participatory observation, documentation, and video analysis. The findings reveal that Ustadz Nuzul Dzikri employs a thematic method grounded in authentic hadiths, delivered in a systematic and accessible style. This approach successfully integrates classical Islamic scholarship with contemporary da'wah communication practices, resonating strongly with urban digital audiences and addressing the evolving demands of Islamic propagation in the era of new media